Risk of hepatitis B virus reactivation following treatment with abatacept: A retrospective study of international pharmacovigilance databases. (June 2022) - Wang, Jingjing; Zhang, Xin; Geng, Xiaozhen; Shi, Juanjuan; Jia, Xiaoli; Dang, Shuangsuo; Wang, Wenjun
Summary: Background: Abatacept is a selective T-cell costimulation modulator approved for the treatment of rheumatoid arthritis, juvenile idiopathic arthritis, and psoriatic arthritis. Reports were recently published on hepatitis B virus reactivation (HBVr) in patients who were treated with abatacept. However, the literature is limited to case reports and series, and no study has investigated the relationship between HBVr and abatacept using extensive population-based databases. Methods: Using the United States Food and Drug Administration Adverse Event Reporting System (FAERS) database, we collected all cases of HBVr between Jan 1, 2006 and June 30, 2021, for abatacept and other drugs. Disproportionality was analysed using the reporting odds ratio (ROR), which was considered significant when the lower limit of the 95% CI was >1. We also conducted a confirmatory analysis in the European pharmacovigilance database, EudraVigilance. Findings: During the study period, 77, 669 adverse cases were reported for abatacept use. There were 2889 reports of HBVr with any drug during this period, of which 55 were reported with abatacept. The ROR for HBVr with abatacept was significantly elevated at 4·80 (95% CI 3·68–6·27). All 55 cases of HBVr with abatacept were reported as serious adverse events. Of them, six individuals were hospitalised and four died. Among 832 reports of HBVr with any drug in EudraVigilance, 43 were reported with abatacept; the ROR was 8·99 (95% CI 6·61–12·23). Interpretation: We identified a positive signal between abatacept exposure and HBVr. Future prospective studies should further confirm the relationship and provide evidence to develop strategies involving pre-treatment screening, monitoring, and utilisation of antiviral prophylaxis when using abatacept in patients with rheumatic diseases. Funding: This work was supported by the Fundamental Research Funds for Central Universities (xjh012019063).